2016
DOI: 10.1016/j.electacta.2016.08.058
|View full text |Cite
|
Sign up to set email alerts
|

Sodium ion storage in reduced graphene oxide

Abstract: Sodium ion storage in reduced graphene oxide, Electrochimica Acta http://dx.doi.org/10. 1016/j.electacta.2016.08.058 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during the production process errors may be discovered which could affect the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(29 citation statements)
references
References 55 publications
0
29
0
Order By: Relevance
“…The diameter of Na + (0.98 Å) is larger than that of Li + (0.69 Å), which makes insertion of Na + into the interlayer of graphite difficult. Recently, as alternative carbon materials, various amorphous carbon materials such as one‐dimensional (1 D) carbon nanofibers/nanotubes, two‐dimensional (2 D) carbon nanoplates, heteroatom‐doped graphene, and three‐dimensional (3 D) porous carbon nanostructures have shown promise as anode materials for SIBs, owing to their large interlayer spacings and disordered structures, which can afford abundant sodium‐ion storage sites. Moreover, a number of elementary substances (P, Sn, Sb, etc.…”
Section: Introductionmentioning
confidence: 99%
“…The diameter of Na + (0.98 Å) is larger than that of Li + (0.69 Å), which makes insertion of Na + into the interlayer of graphite difficult. Recently, as alternative carbon materials, various amorphous carbon materials such as one‐dimensional (1 D) carbon nanofibers/nanotubes, two‐dimensional (2 D) carbon nanoplates, heteroatom‐doped graphene, and three‐dimensional (3 D) porous carbon nanostructures have shown promise as anode materials for SIBs, owing to their large interlayer spacings and disordered structures, which can afford abundant sodium‐ion storage sites. Moreover, a number of elementary substances (P, Sn, Sb, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Wen et al reported a reversible capacity of 280 mAh g −1 at a current density of 20 mA g −1 through increasing the interlayer spacing to 4.3 Å [13]. Kumar et al recently observed that the rGO anode delivered a discharge capacity of 272 mA h g −1 at a current density of 50 mA g −1 [14]. Thus, the results indicated rGO as a potential electrochemically active material for SIBs.…”
mentioning
confidence: 99%
“…Graphene with a monolayer of SP 2 carbon atoms located in 2D honeycomb network, is a very promising carbon material to improve the performance of NCO because it is electrically conductive and suitable for wrapping/encapsulating/supporting NCO particles to alleviate the volume changes. [59][60][61][62][63] Apart from stabilizing TMOs, graphene itself can reversibly store sodium ions the surfaces, edges and covalent sites of graphene sheets, 64 and thereby, beneficial for energy storage. Moreover, doping nitrogen (N) and creating pores in graphene can improve the wettability between graphene and an organic electrolyte, 65 to facilitate the transport of sodium ions and electrons.…”
Section: W\ Significance and Research Objectivesmentioning
confidence: 99%
“…The individual graphene sheets can store ions on their surfaces, edges and covalent sites, 64 has been reported as cathode electrode for NICs as briefly reviewed in the section 2.1.2.…”
Section: Graphene-based Materialsmentioning
confidence: 99%
See 1 more Smart Citation